Stem Cell Therapy in Lysosomal Storage Diseases - Boelens, Jaap Jan.; Wynn, Robert; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana Press, 2013)
Stem Cell therapy for lysosomal diseases (LSDs) is developing rapidly. This volume discusses the history, current practice and future perspectives of stem cells in inborn errors of metabolism (IEM) and provides an international perspective on progress, limitations, and future directions (e.g. gene therapy, iPS, ES) in the field. Beginning with an overview of these diseases, the book covers the breadth of this topic from treatment options, bone marrow transplantation, and alternative treatment options, through long-term outcomes and future perspectives.
1. Lysosomal Diseases and Therapeutic Options: An Overview -- 2. Alternative Treatment Options: Enzyme Replacement and Small Molecule Therapies -- 3. Hematopoietic Cell Transplantation in Inborn Errors of Metabolism -- 4. Allogeneic Hematopoietic Stem Cell Transplantation in Lysosomal Storage Disorders: Long Term Neurodevelopmental and Somatic Outcome -- 5. Hematopoietic Stem Cell Gene Therapy for Lysosomal Storage Disorders: Expected Benefits and Limitations -- 6. Alternative Future Therapies for Lysosomal Storage Diseases: Embryonic Stem Cell- and Induced Pluripotent Stem Cell Therapy -- 7. New Directions and Conclusions.
Keywords: Life sciences; Human genetics; Cytology; Stem cells; Life Sciences; Stem Cells; Cell Biology; Human Genetics